Source apportionment of Pb-containing particles in Beijing during January 2013. (July 2017) - Cai, Jing; Wang, Jiandong; Zhang, Yanjun; Tian, Hezhong; Zhu, Chuanyong; Gross, Deborah S.; Hu, Min; Hao, Jiming; He, Kebin; Wang, Shuxiao; Zheng, Mei
Abstract: Although leaded gasoline has been banned in some megacities in China since 1997 and nationally since 2000, atmospheric lead (Pb) pollution is still an important issue in China, as its concentration in megacities such as Beijing remains high. To measure the Pb concentration and identify sources of Pb-containing particles in Beijing during January 2013, both an online Single Particle Aerosol Mass Spectrometer (SPAMS) and offline filters analyzed by inductively coupled plasma-mass spectrometer (ICP-MS) were used at a monitoring site on the Peking University (PKU) campus. The average Pb concentration in PM2.5 was 370 ng/m 3 in January 2013 and the highest daily concentration was as high as 1.3 μg/m 3 during our sampling period. Based on the mass spectra from the SPAMS, these particles were classified into 4 major types, including NO3 -rich (61%), ECOC-rich (18%), Fe-rich (14%), and SO4 -rich (7%). Results from this study suggest that combustion processes and the iron/steel industry were the major primary sources of Pb in Beijing. On clean days, the importance of the primary combustion particle type (ECOC-rich) increased, while during severe haze episodes, Pb-containing particles mixed with secondary ions and Fe were dominant. Based on estimates from the CMAQ model, on average 45% of Pb in PM2.5 in urban Beijing was transported in January 2013, with a much higher percent transported during the haze episodes. The percentage of transported Pb increased with the concentration of Pb and PM2.5, indicating that emissions from the surrounding areas need to be controlled during high Pb episodes in Beijing in winter. Graphical abstract: Highlights: High atmospheric Pb concentration was observed in January 2013, Beijing. 4 types and 3 sources (combustion, iron industry and aging) of Pb were identified. 45% of the Pb particles were transported (much higher during haze episodes). Abstract : Four particle types and three major sources of atmospheric Pb were identified in January 2013 in Beijing. 45% of the Pb was transported (much higher during haze episodes).